The jurisprudence of labour and industrial laws in Malaysia: conservatism or activism in court judgements? - Sanjay Kumar, Kanchanlal (2017)
The area of judicial activism in labour and industrial jurisprudence is not a widely undertaken or debated area of law in Malaysia. Judicial activism as opposed to conservatism often depends on decisions pronounced by competent courts dealing with labour and industrial matters. There are decisions which strictly abide by precedential authority and there are decisions which deal with more flexible intrusions into legislative authority. The research problem is that majority of the resolutions made at the labour court or industrial court in Malaysia are more prone towards conservatism rather than activism. The research objective is to inquire whether such decisions in turn affect an employer and employee relationship in a social justice context. It is to be noted that Malaysia is a signatory to the International Labour Organisation (ILO) which sets minimum standards to be adhered by each country in governing its labour and industrial laws. The research was undertaken for a detailed study of statutes and law cases related to labour and industrial matters in Malaysia to determine whether the judiciary is indeed favourable to conservatism. To this end, analysing statutory provisions such as the Employment Act 1955 and Industrial Relations Act 1967 as interpreted through cases in the labour court, industrial court and civil court gave an end picture of the research objective. Neither could we deny nor be unaware of the influence of colonial laws of England on our jurisprudence which to date has remained more conservative compared to the American and Indian judicial systems. The importance of this research is to enable more just labour and industrial law practices for the ultimate good of social justice and perhaps a reformulation of these laws. The research findings indicated that there was a lack of judicial activism in Malaysia with an inclination towards conservatism. With this finding, recommendations were made in important areas of labour and industrial laws in order to encourage amendments, introduction of new legislations by the legislature and strengthening the judicial decisions by the judiciary.